Theoretical and experimental investigations of synthesis and catalytic properties of nano-dispersed titanium oxide photocatalysts modified with spectral sensibilizing additives - Sizeneva, I.P.; Lebedeva, I.I.; Kiselkov, D.M. (Perm Federal Research Centre Journal, 2017)
A method of producing doped titanium dioxide of anatase modification of a globular structure is developed, which is thermally stable at a temperature of 600ºC. The method is based on the co-hydrolysis of titanium tetrachloride, and small amounts of cobalt and iron inorganic salts in ammonium medium at room temperature, wherein anatase stabilization occurs through the formation of an intermediate structure Ti-O-Me. It has been found that doping of titanium dioxide by transitional metal ions leads to a shift of the absorption band edge in the diffuse reflectance spectra to the visible region of the spectrum, which is accompanied by a decrease in the value of the band gap. It has been established that the introduction of fluorine into the crystal lattice of titanium dioxide does not lead to a narrowing of the band gap, but helps to stabilize the anatase modification of TiO2 and that the width of the band gap of TiO2-C samples significantly depends on the receiving method and subsequent heat treatment conditions.